DAMPAK KEBIJAKAN VISA ON ARRIVAL (VOA) DAN BEBAS VISA KUNJUNGAN (BVK) TERHADAP ASPEK SOSIAL-BUDAYA INDONESIA - Nurfara, Najma Afifa; Setiawan, Nisa Aulia Nur; Putra, Dzaky Huda Ari Sumenang; Radyahadi, M. Fadhlan; Izzati J, Athiyyah (Pusat Perencanaan dan Pengembangan Kepariwisataan, 2024)
The Indonesian government has implemented Visa on Arrival (VoA) and Visa-Free Visit (BVK) policies. These facilities make it easier for prospective international tourists to explore Indonesia and can have both positive and negative impacts within its scope. This research is depicted through phenomena using a qualitative descriptive design and data collection through reports, news, and other supporting documents via literature study. The interaction between international tourists and local communities can lead to friction resulting in criminal acts. This can undermine Indonesia's resilience and security in socio-cultural aspects. Many criminal acts have been committed by international tourists, including an incident where a female foreign national disrupted a traditional Balinese dance performance and was not wearing clothing.